2018
DOI: 10.2147/ijn.s155532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogenated TiO<sub>2</sub> nanotube arrays on protein adsorption and compatibility with osteoblast-like cells

Abstract: BackgroundModified titanium (Ti) substrates with titanium dioxide (TiO2) nanotubes have broad usage as implant surface treatments and as drug delivery systems.MethodsTo improve drug-loading capacity and accelerate bone integration with titanium, in this study, we hydrogenated anodized titanium dioxide nanotubes (TNTs) by a thermal treatment. Three groups were examined, namely: hydrogenated TNTs (H2-TNTs, test), unmodified TNTs (air-TNTs, control), and Ti substrates (Ti, control).ResultsOur results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…It has been reported that protein adsorption on TiO 2 nanotube surfaces is dependent on surface properties. 50,51 The TiO 2 nanotubes with larger diameters possessed greater interaction energies, leading to better protein adsorption and thus regulating cell responses. 52 In addition to the influence of nanotube diameter, it is possible that the bioactivity of 105 nm TiO 2 nanotubes, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that protein adsorption on TiO 2 nanotube surfaces is dependent on surface properties. 50,51 The TiO 2 nanotubes with larger diameters possessed greater interaction energies, leading to better protein adsorption and thus regulating cell responses. 52 In addition to the influence of nanotube diameter, it is possible that the bioactivity of 105 nm TiO 2 nanotubes, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al reported that the difference of nanotube diameters can severely influence cell adhesion and spreading of mesenchymal stem cells (Park, Bauer, Mark, & Schmuki, 2007). Lu et al proved that the hydrogenated TiO 2 nanotubes upon thermal treatment could greatly prove the loading capacity of bioactive molecules and subsequent MG‐63 cell proliferation (Lu et al, 2018). Chen et al modified TiO 2 nanotube arrays with functional proteins (bone morphogenetic protein 2 and sclerostin antibody) to promote osteoblast differentiation of mesenchymal stem cells and bone fracture recovery (Chen et al, 2019; Lai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 nanotubes are of great interest due to their excellent physical, mechanical and biological properties. Previous studies have reported that nanotubes enhance the protein adsorption and osteoblast cell attachment which improves bioactivity [23,24]. In this study, we fabricated nanotubes on the surface of both CP-Ti and Ti-6Al-4V using experimental different conditions.…”
Section: Discussionmentioning
confidence: 99%